2017
DOI: 10.1111/ejn.13646
|View full text |Cite
|
Sign up to set email alerts
|

GPR88 in A2A receptor‐expressing neurons modulates locomotor response to dopamine agonists but not sensorimotor gating

Abstract: The orphan receptor, GPR88, is emerging as a key player in the pathophysiology of several neuropsychiatric diseases, including psychotic disorders. Knockout (KO) mice lacking GPR88 throughout the brain exhibit many abnormalities relevant to schizophrenia including locomotor hyperactivity, behavioral hypersensitivity to dopaminergic psychostimulants and deficient sensorimotor gating. Here, we used conditional knockout (cKO) mice lacking GPR88 selectively in striatal medium spiny neurons expressing A2Areceptor t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
64
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(64 citation statements)
references
References 34 publications
0
64
0
Order By: Relevance
“…Accordingly, CMV- Gpr88 mice have been shown to have altered transcriptional profiles in these structures where both GPR88 and D1R are expressed (Meirsman et al, 2016b). Most importantly, recent studies using CMV- Gpr88 mice have shown impaired multisensory processing (Ehrlich et al, 2018) and sensorimotor gating (Meirsman et al, 2017) that, coupled with altered sensorimotor and cortico-striatal functional connectivity (Arefin et al, 2017), suggest a role of this receptor in the integration and processing of sensory information. Interestingly, it has also been suggested that modifications of the striato-cortical circuitry may underlie the hyperactivity observed in CMV -Gpr88 mice (Arefin et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, CMV- Gpr88 mice have been shown to have altered transcriptional profiles in these structures where both GPR88 and D1R are expressed (Meirsman et al, 2016b). Most importantly, recent studies using CMV- Gpr88 mice have shown impaired multisensory processing (Ehrlich et al, 2018) and sensorimotor gating (Meirsman et al, 2017) that, coupled with altered sensorimotor and cortico-striatal functional connectivity (Arefin et al, 2017), suggest a role of this receptor in the integration and processing of sensory information. Interestingly, it has also been suggested that modifications of the striato-cortical circuitry may underlie the hyperactivity observed in CMV -Gpr88 mice (Arefin et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Despite the established overall function of striatal GPR88 in brain functions and deficits (in humans and mice), no study to date has directly compared the specific role of GPR88 in D1R-and D2R-MSNs. A conditional KO mouse line for GPR88 in D2R-MSNs was developed in a previous study, using a A 2A R-Cre driver line (A 2A R -Gpr88 mice), and mutant mice showed hyperactive behavior, decreased anxiety-like behaviors and increased locomotor response to dopaminergic agonists (Meirsman et al, 2016a, 2017). In this study, we have generated conditional Gpr88 KO for D1R-MSNs (D1R- Gpr88 mice), and compared behavioral responses of D1R- Gpr88 with those of A 2A R -Gpr88 mice and total KO (CMV- Gpr88 ) mice.…”
Section: Introductionmentioning
confidence: 99%
“…Previous behavioral studies of Gpr88 -/- mice have highlighted deficits mainly related to striatal function, and deficits in sensorimotor gating (Logue et al 2009; Meirsman et al 2017), however responses of these mice to sensory stimuli have not been examined otherwise. We therefore designed a test battery to challenge the integration of olfactory, somatosensory and visual sensory responses, all related to the remarkable receptor expression pattern in the cortex (Figure 8A).…”
Section: Resultsmentioning
confidence: 99%
“…Altogether, these findings suggest that GPR88 levels are finely regulated by sophisticated mechanisms that depend on the brain area and most likely involve a variety of signaling cascades. Considering the physiological relevance of GPR88, several lines of GPR88 KO mice were created to assess the gene function globally or in specific neuronal populations [ 88 , 89 , 90 , 202 ]. GPR88 has been shown to be densely expressed in the CeA, a brain region that controls emotional processing.…”
Section: Systematic Analysis Of Ogpcrs In Anxiety and Mood Disordementioning
confidence: 99%